Development of cyanopyridine–triazine hybrids as lead multitarget anti-Alzheimer agents. Issue 12 (15th June 2016) - Maqbool, Mudasir; Manral, Apra; Jameel, Ehtesham; Kumar, Jitendra; Saini, Vikas; Shandilya, Ashutosh; Tiwari, Manisha; Hoda, Nasimul; Jayaram, B.
Graphical abstract: Highlights: A series of new cyanopyridine–triazine hybrids were developed as persuasive multifunctional anti-AD agents. Docking studies were performed on reported crystal structures of human acetylcholinesterase and butyrylcholinesterase. In vitro inhibitory potencies against acetylcholinesterase, and butyrylcholinesterase were assessed. Aβ1–42 disaggregation, oxygen radical absorbance, cytotoxicity, neuroprotection tests were also performed. Abstract: A series of new cyanopyridine–triazine hybrids were designed, synthesized and screened as multitargeted anti-Alzheimer's agents. These molecules were designed while using computational techniques and were synthesized via a feasible concurrent synthetic route. Inhibition potencies of synthetic compounds4a –4h against cholinesterases, Aβ1–42 disaggregation, oxidative stress, cytotoxicity, and neuroprotection against Aβ1–42 -induced toxicity of the synthesized compounds were evaluated. Compounds4d and4h showed promising inhibitory activity on acetylcholinesterase (AChE) with IC50 values 0.059 and 0.080 μM, respectively, along with good inhibition selectivity against AChE over butyrylcholinesterase (BuChE). Molecular modelling studies revealed that these compounds interacted simultaneously with the catalytic active site (CAS) and the peripheral anionic site (PAS) of AChE. The mixed type inhibition of compound4d further confirmed their dual binding nature in kinetic studies. Furthermore, the results from neuroprotection studies of most potent compounds4d and4h indicate that these derivatives can reduce neuronal death induced by H2 O2 -mediated oxidative stress and Aβ1–42 induced cytotoxicity. In addition, in silico analysis of absorption, distribution, metabolism and excretion (ADME) profile of best compounds4d and4h revealed that they have drug like properties. Overall, these cyanopyridine–triazine hybrids can be considered as a candidate with potential impact for further pharmacological development in Alzheimer's therapy.